Economic Growth and Income Distribution - Strassmann, W. Paul (Quarterly Journal of Economics, 1956)
I. Introduction, 425. — II. Economic growth and growing income equality, 427. — III. Empirical evidence, 432. — IV. Conclusion, 439.